John Dillinger : the life and death of America's first celebrity criminal - Matera, Dary, 1955- (New York : Carroll & Graf Publishers, 2005)
The FBI's first "Public Enemy," Dillinger was dubbed "The Jackrabbit" because of the way he leaped over bank cages and railings. His bank-robbing gang cut a criminal swath yet to be equaled. They became so famous in the 1930s that throngs of excited spectators would block the route to their getaway cars. When caught, Dillinger staged the most harrowing prison escapes imaginable--only to finally be betrayed by the infamous "Lady in Red." Biographer Matera brings to light new information, including bank robberies never before reported; detailed plans for major crimes that Dillinger nearly implemented; and the revelation that the "Lady in Red" was actually a police plant. With access to thousands of detailed accounts, and pages of telling photographs, Matera's definitive book describes every robbery, shoot-out, and prison escape in fine detail.--From publisher description.
Includes bibliographical references (page 372-405) and index.
Keywords: Dillinger, John, -- 1903-1934.; Criminals -- Middle West -- Biography; Gangs -- Middle West